Polyglutamine Neurodegeneration: Protein Misfolding Revisited - Williams, Aislinn J. (2008)
Polyglutamine diseases are a major cause of neurodegenerative disease worldwide. Recent studies highlight the importance of protein quality control mechanisms in regulating polyglutamine-induced toxicity. Drawing on these studies, we propose a model of disease pathogenesis that integrates current understanding of the role of protein folding in polyglutamine disease. We also incorporate new findings on other age-related neurodegenerative diseases in an effort to explain how protein aggregation and normal aging processes might be involved in polyglutamine disease pathogenesis.